2020
DOI: 10.3390/ph13080184
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vitro Toxicology of Novel Cytoprotective Short-Chain Naphthoquinones

Abstract: Short-chain quinones (SCQs) have been identified as potential drug candidates against mitochondrial dysfunction, which largely depends on the reversible redox characteristics of the active quinone core. We recently identified 11 naphthoquinone derivatives, 1–11, from a library of SCQs that demonstrated enhanced cytoprotection and improved metabolic stability compared to the clinically used benzoquinone idebenone. Since the toxicity properties of our promising SCQs were unknown, this study developed multiplex m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…Since the safety properties of ASP were unknown, this study aimed to assess the effects of the natural compound on cellular viability using the human hepatocarcinoma cell line HepG2. This cell line is widely used for toxicity studies due to its high phenotypic stability for robust and reproducible outcomes, although HepG2 cells are less metabolically active compared with primary hepatocytes and other cell lines such as C3A or HepaRG [36].…”
Section: Discussionmentioning
confidence: 99%
“…Since the safety properties of ASP were unknown, this study aimed to assess the effects of the natural compound on cellular viability using the human hepatocarcinoma cell line HepG2. This cell line is widely used for toxicity studies due to its high phenotypic stability for robust and reproducible outcomes, although HepG2 cells are less metabolically active compared with primary hepatocytes and other cell lines such as C3A or HepaRG [36].…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to characterize the in vitro bioactivities of a library of 103 recently described short-chain naphthoquinones (SCQs) [ 22 , 24 , 26 ] to investigate the underlying mechanism(s) of SCQ-dependent cytoprotection. For this purpose, the current study employed not only the previously reported endpoints of cytoprotection and normalization of cellular ATP levels [ 26 ], but also assessed additional bioactivities of quinones that are indicative of mitochondrial function, compound bioactivation, expression or activities of cytoprotective proteins (Lin28A, Hsp70, HDAC6), oxidative damage and DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the only synthetic quinone clinically approved for a single mitochondrial disease is the benzoquinone idebenone [ 18 ], which showed some activity to protect against vision loss and restored visual acuity and color vision in LHON patients [ 19 , 20 , 21 ]. Although idebenone is safe and well tolerated in vitro (IC 50 = 151.7 μM, 24 h) [ 22 ] and in vivo (2250 mg/d, 14 d) [ 23 ], it is not an ideal drug as it shows low solubility (logP = 1.24, logD = 3.57) and more importantly is characterized by very low metabolic stability in vitro ( t 1/2 = 2 h, 40 μM) [ 24 ] and in vivo ( t 1/2 = 3 h, 150 mg) [ 25 ], which significantly restrict its therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, more than 148 novel naphthoquinones derivatives of short-chain quinones (SCQs) have been synthesised and screened in vitro for their cytoprotective activity against mitochondrial dysfunction ( Woolley et al, 2019 ). Among them, 16 amide-linked naphthoquinones showed high metabolic stability, low toxicity, and better cytoprotection in vitro ( Woolley et al, 2019 ; Feng et al, 2020a ; Feng et al, 2020b ). Indeed, one of the newly synthesised naphthoquinones (UTA77) restored vision loss in vivo in mitochondrial dysfunction-related pathology, i.e., diabetic retinopathy ( Daniel et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%